Toward a Situational Model for Regulating International Crimes - Woods, Andrew Keane (2012)
The international criminal regime, as currently conceived, relies almost exclusively on the power of backward-looking criminal sanctions to deter future international crimes. This model reflects the dominant mid-century approach to crime control, which was essentially reactive. Since then, domestic criminal scholars and practitioners have developed and implemented new theories of crime control—theories notable for their promise of crime prevention through ex ante attention to community and environmental factors. Community policing crime prevention through environmental design, and related situational approaches to crime control have had a significant impact on the administration of domestic criminal law. This Article evaluates the implications of these approaches for the international criminal regime. Despite the significant distinctions between international and domestic crimes, there are important similarities—most notably, the finding that environmental factors play a key role in the commission of both sorts of crimes. This finding creates space for the situational turn at the international level. Applying this model to the international regime has implications for how we understand and design tactics aimed at preventing international crimes ex ante. It also has real and theoretical implications for ex post justice